The IMPLEMENTATION OF ACCOUNTING POLICY OF FIXED ASSETS ACCORDING TO INDONESIAN FINANCIAL ACCOUNTING STANDARD NUMBER 16 AT PT. GT - Kendy, Maria Advencia; Malau, Melinda; Tampubolon, Emma (Buletin Ekonomi, 2018)
This final report is made to know the implementation of accounting policy of fixed assets according to Standar Akuntansi Keuangan Indonesia Nomor 16 at PT. GTI. Data collection techniques used were obsevation and interview. The method used in this observation is a descriptive method, comparing problems directly on the field with existing theory. Based on the results of research that has been done by the author. It can be concluded that the application of fixed asset accounting policy is guided by Standar Akuntansi Keuangan Indonesia Nomor 16. However, for fixed asset accounting still needs to be adjusted, especially in disposal of fixed asset for sale and determining depreciation method,as it has an effect on gross profit earned by the company over the economic life of fixed asset. Keywords : fixed asset, accounting policies, Standar Akuntansi Keuangan Indonesia Nomor 16.